Newborn Screening for Sickle Cell Disease in Europe - Yvonne Daniel; Jacques Elion; Bichr Allaf; Catherine Badens; Marelle J. Bouva; Ian Brincat; Elena Cela; Cathy Coppinger; Mariane de Montalembert; Béatrice Gulbis; Joan Henthorn; Olivier Ketelslegers; et al. (MDPI AG, 2019)
The history of newborn screening (NBS) for sickle cell disease (SCD) in Europe goes back almost 40 years. However, most European countries have not established it to date. The European screening map is surprisingly heterogenous. The first countries to introduce sickle cell screening on a national scale were France and England. The French West Indies started to screen their newborns for SCD as early as 1983/84. To this day, all countries of the United Kingdom of Great Britain and Northern Ireland have added SCD as a target disease to their NBS programs. The Netherlands, Spain and Malta also have national programs. Belgium screens regionally in the Brussels and Liège regions, Ireland has been running a pilot for many years that has become quasi-official. However, the Belgian and Irish programs are not publicly funded. Italy and Germany have completed several pilot studies but are still in the preparatory phase of national NBS programs for SCD, although both countries have well-established concepts for metabolic and endocrine disorders. This article will give a brief overview of the situation in Europe and put a focus on the programs of the two pioneers of the continent, England and France.